PRICING AND INVESTMENT STRATEGY FOR DIGITAL TECHNOLOGY IN A SUPPLY CHAIN - Nguyen, Thi My Hanh; Chen, Jen-Ming (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
This study addresses the problem of the pricing and investment strategy for smart technology under a supply chain with one manufacturer and one retailer. The models are constructed to investigate the strategic choices of supply chain members for investing in digital/smart technology under three scenarios: the M–system, wherein only the manufacturer fully pays for the investment cost; the S–system, wherein the manufacturer and retailer share the investment cost; and the R–system, wherein the retailer fully pays for the investment cost. We formulate analytical models to determine the optimal wholesale price, retail price and investment strategy in a Stackelberg game setting. Our findings show that the S–system is the most appropriate choice for both the manufacturer and retailer. We also suggest the appropriate investment sharing ratio to achieve Pareto improvement under such an arrangement.